2014
DOI: 10.1177/1060028014520957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Introducing Procalcitonin on Antimicrobial Therapy Duration in Patients With Sepsis and/or Pneumonia in the Intensive Care Unit

Abstract: Background: Utilizing procalcitonin (PCT) levels to limit antimicrobial overuse would be beneficial from a humanistic and economic perspective. Objective: To assess whether introducing PCT at a teaching hospital reduced antimicrobial exposure in critically ill patients. Methods: Patients wereadmitted to the intensive care unit (ICU) for >72 hours with sepsis and/or pneumonia. PCT levels were drawn on admission to the ICU or with new suspected infection, with at least 1 PCT level being drawn at least 48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…The authors cited modest adherence and lack of serial PCT measurements as potential factors contributing to the lack of observed benefits. In other studies, adherence to PCT algorithms varies greatly, ranging from 47–97% …”
Section: Challenges Implementing Pct Monitoringmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors cited modest adherence and lack of serial PCT measurements as potential factors contributing to the lack of observed benefits. In other studies, adherence to PCT algorithms varies greatly, ranging from 47–97% …”
Section: Challenges Implementing Pct Monitoringmentioning
confidence: 98%
“…Among critically ill patients, PCT monitoring also demonstrated a reduction in antibiotic therapy duration when compared with standard care, ranging from 1.7-3.8 days (Table 4). 37,[50][51][52][53][54][55] A multicenter randomized trial conducted in 1546 ICU patients with assumed or probable infection noted a 5.4% absolute difference in 28day mortality between PCT and standard-of-care groups (95% CI 1.2-9.5, p=0.0122) and a 7.4% absolute difference in 1-year mortality (95% CI 1.3-13.8, p=0.0188). 51 Most studies conducted in critically ill or septic patients showed no difference in overall hospital or ICU length of stay with PCT monitoring.…”
Section: Critical Illness And/or Sepsismentioning
confidence: 99%
“…Indeed, when a PCT algorithm was combined with twice/week infectious disease stewardship rounds in a randomized trial in the antibiotic continuation setting, compliance with PCT algorithm recommendations was above 97% . In an ICU patient population with low mortality risk, implementation of PCT assays partnered with an active antimicrobial stewardship program in clinical practice was shown to decrease antimicrobial use and hospital length of stay . Previous investigators have, at least partially, attributed PCT algorithm overruling to the reluctance of clinicians to comply with algorithm recommendations in patients who have not clinically improved (and instead relying predominantly on their clinical judgment) .…”
Section: Discussionmentioning
confidence: 99%
“…10 In an ICU patient population with low mortality risk, implementation of PCT assays partnered with an active antimicrobial stewardship program in clinical practice was shown to decrease antimicrobial use and hospital length of stay. 27 Previous investigators have, at least partially, attributed PCT algorithm overruling to the reluctance of clinicians to comply with algorithm recommendations in patients who have not clinically improved (and instead relying predominantly on their clinical judgment). 5 In fact, the expert authors of a systematic review recommended empirical overruling of a PCT algorithm in a critically ill patient in the initiation setting when a clinical suspicion for infection exists and continuation of antibiotics in the follow-up setting when patients are clinically unstable.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that the savings associated with PCT-guided care is not associated with any meaningful differences in quality, which has been a consistent finding of clinical effectiveness studies of PCT to date [5,30,34,38,52,78,79]. Moreover, our calculations take into account the costs of the tests and the administration of the tests.…”
Section: Discussionmentioning
confidence: 99%